North Macedonia in the Western Balkans: Between regional and European integration - Kitevski, Goran; Mijalova, Katerina (UTMS Journal of Economics, 2025)
The main subject of the study is the position of North Macedonia within the European Union (EU) enlargement framework and the geopolitical configuration of the Western Balkans, conceptualised not as a geographic entity but as a political category defined by non-membership. Although designated a candidate state in 2005 and formally approved for accession negotiations in 2020, North Macedonia remains the most protracted accession case in the region. The Western Balkans, initially incorporated into the EU enlargement agenda through the Stabilisation and Association Process, remain institutionally framed as a transitional space expected to converge with the Union. While the 2003 Thessaloniki Summit affirmed the region’s membership perspective, post-Thessaloniki developments were marked by procedural revision, enlargement fatigue, and (geo)political recalibration. Comparative analysis of the Commission’s 2025 reports confirm that North Macedonia is not substantially lagging in acquis alignment relative to Albania and other WB6 countries, but remains constrained by unresolved identity-based conditions
Keywords: Western Balkans; European Union enlargement; North Macedonia; Prespa Agreement; candidate status; constitutional amendments